A portable device for single point strain analysis in sheet metal forming processes. (October 2022) - Wankhede, Pankaj; Narayanaswamy, Nara Guru; Kurra, Suresh; Priyadarshini, Amrita
Graphical abstract: Abstract: Strain measurement is one of the basic techniques in sheet metal forming for quantifying the deformation of a material under the effects of various loading conditions. The main components in the automatic strain measurement system are the image acquisition hardware and image processing software. This paper presents an automatic single point strain analysis system for sheet metal forming applications. The proposed system is very portable and consists of a USB microscope with different end caps for image acquisition. The software system was developed using Python – OpenCV library and provided with a graphical user interface (GUI).